Application of Simple Refraction Correction Method for Shallow Coastal Bathymetric Mapping Based on UAV-Photogrammetry - I GD Yudha Partama; I Gede Gegiranang Wiryadi; I Dewa Gede Agung Pandawana; Agus Sukma Yogiswara (Geosfera Indonesia, 2023)
Shallow coastal bathymetric data has an important role in various applications, especially in maritime and coastal management fields. Various survey techniques to produce such data have been carried out by several researchers, one technique that is cheap, covers the wide area, flexible, and produces high-resolution bathymetric data is UAV-photogrammetry. However, this technique is affected by refraction effects that cause the estimated depth of underwater objects to be shallower than fact, thus reducing the accuracy of the bathymetric model. Therefore, the objective of this study is to present a simple refraction correction method based on the Least-Square method. To test the reliability of the method, the accuracy of the model is compared with two other methods (without correction and using a correction factor = 1.34). In addition, the effectiveness of the method was also tested through its application in various survey conditions. Overall, the proposed method outperforms the two existing methods. It is also very effective in reducing the error value during high tide conditions by up to 70%. The height of the UAV does not significantly affect the accuracy of the correction model, so in this case it is recommended to use an altitude of 100 m for survey efficiency.